2021
DOI: 10.1039/d0ta09788h
|View full text |Cite
|
Sign up to set email alerts
|

A vast exploration of improvising synthetic strategies for enhancing the OER kinetics of LDH structures: a review

Abstract: In last few decades, Layered Double Hydroxides (LDHs) based materials have taken much attention of the researchers due to their significant advancements in enabling efficient oxygen evolution. Having exceptional layered...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
173
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(193 citation statements)
references
References 151 publications
0
173
0
Order By: Relevance
“…Hydroxides, oxyhydroxides, and layered double hydroxides (LDHs) of TM oxides, such as Ni, Co, Fe, Mn, and V, are highly active in electrocatalytic oxygen evolution reaction. 86,117,118 They exhibit typical layered stacking conformation with proton sandwiching between layers, and the metal is centered in the octahedron surrounded by oxygen anions at the corners as MO 6 . 117 Some representative hydroxides and their catalytic performances are listed in Table 2.…”
Section: Hydroxidesmentioning
confidence: 99%
“…Hydroxides, oxyhydroxides, and layered double hydroxides (LDHs) of TM oxides, such as Ni, Co, Fe, Mn, and V, are highly active in electrocatalytic oxygen evolution reaction. 86,117,118 They exhibit typical layered stacking conformation with proton sandwiching between layers, and the metal is centered in the octahedron surrounded by oxygen anions at the corners as MO 6 . 117 Some representative hydroxides and their catalytic performances are listed in Table 2.…”
Section: Hydroxidesmentioning
confidence: 99%
“…[40,42] Additionally, it has been reported that the high electrical conductivity of the active material is a critical factor in achieving higher catalytic activities, which results in low R s values. [44,45] For example, the NiFe LDH nanoarrays with improved electrical conductivity by modulating the density of oxygen vacancies on the materials' surface showed improved catalytic activities with a marked reduction in R s values despite no notable geometrical changes. [46] In particular, very similar metal hydroxide composition and structure between NiFe LDH and EP Ni−cotton surface (i.e., Ni(OH) 2 ) allow for stable connection through strong interfacial interactions, enabling negligible contact resistance and fast charge transfer as well as stable performance retention.…”
Section: Oer Textile Electrode Using Electroplated Nifementioning
confidence: 99%
“…Oxygen evolution reaction (OER) catalysis constitutes the bottleneck for water splitting, solar cells, metal-air batteries, fuel cells and other renewable energy systems [1][2][3] due to the sluggish kinetics of the OER, which involves a complex fourelectron/proton transfer process. 4,5 Although noble metal oxides like IrO 2 and RuO 2 show excellent catalytic performance for the OER, their widespread development is restricted by their high cost and scarcity.…”
Section: Introductionmentioning
confidence: 99%